1997
DOI: 10.1002/j.1875-9114.1997.tb03674.x
|View full text |Cite
|
Sign up to set email alerts
|

Mirtazapine: An Antidepressant with Noradrenergic and Specific Serotonergic Effects

Abstract: Mirtazapine is a unique antidepressant that refines the specificity of effects on noradrenergic and serotonergic systems. It is an antagonist of presynaptic α2‐adrenergic autoreceptors and heteroreceptors on both norepinephrine and serotonin (5‐HT) presynaptic axons, plus is a potent antagonist of postsynaptic 5‐HT2 and 5‐HT3 receptors. The net outcome of these effects is increased noradrenergic activity together with specific increased serotonergic activity, especially at 5‐HT1A receptors. This mechanism of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(20 citation statements)
references
References 42 publications
0
12
0
3
Order By: Relevance
“…For example, mirtazapine is a newly developed antidepressant that increases both serotonergic and noradrenergic activity and early reports suggest that rates of sexual dysfunction with mirtazapine are lower than placebo. 236 Similarly, some evidence suggests that yohimbine, a drug that increases NE activity, may be useful in treating erectile dysfunction and anorgasmia. [237][238][239] Studies suggest that NE is also active during the sexual response cycles of women.…”
Section: Norepinephrinementioning
confidence: 99%
“…For example, mirtazapine is a newly developed antidepressant that increases both serotonergic and noradrenergic activity and early reports suggest that rates of sexual dysfunction with mirtazapine are lower than placebo. 236 Similarly, some evidence suggests that yohimbine, a drug that increases NE activity, may be useful in treating erectile dysfunction and anorgasmia. [237][238][239] Studies suggest that NE is also active during the sexual response cycles of women.…”
Section: Norepinephrinementioning
confidence: 99%
“…They concluded that lowdose ketamine is helpful and safe when added to opioid analgesia in postoperative patients. 4 In a second meta-analysis, Bell et al reported a similar role for ketamine in a postsurgical population. 5 Ketamine has been shown, anecdotally, to help manage a variety of adult opioid-refractory nonsurgical pains as well.…”
Section: Ketamine Infusion For Sickle Cell Crisis Pain In An Adultmentioning
confidence: 94%
“…In addition, mirtazapine blocks presynaptic autoregulatory norepinephrine receptors that facilitate norepinephrine neurotransmission. 3,4 Mirtazapine has a rapid onset to activity relative to other antidepressants. 5,6 Rapid improvement of symptoms in individuals with a short survival time is important.…”
Section: Intolerance To Mirtazapine In Advanced Cancermentioning
confidence: 99%
“…In addition to its primary action, it is also a potent H1-histaminergic blocker, which can cause sedation, increased appetite, and weight gain. [21][22][23] Although weight gain may be an undesirable side effect in most patients, it is helpful in the treatment of certain groups of patients, as in this patient, whose underlying illness has led to poor appetite and unhealthy weight loss. Of note, the Food and Drug Administration has attached a black box warning to the use of mirtazapine as it has been associated with rare worsening depression and suicidal tendencies.…”
Section: Admission Dischargementioning
confidence: 99%